Economic assessment of energy efficiency in residential buildings in Mozambique: case study of Maputo - Chicombo, Adélia Filosa Francisco (Energy Research Centre, 2015)
The world’s energy consumption has been increasing dramatically in recent years. Economic and population growth are said to be the main drivers of this phenomenon. This change is held responsible for the increase in greenhouse gas emissions into the atmosphere, the reduced energy security and the negative socio-economic implications, especially in developing countries. From a sectorial perspective, buildings are part of the large energy consumers, especially the residential sector. It is in this view that measures to reduce this sector’s energy demand has been largely recommended. One of these measures is promoting the deployment of energy efficient buildings combined with the use of energy efficient appliances. The aim of this study was to assess the economic feasibility associated with sustainable buildings with emphasis on the energy efficiency component. The study concentrated on residential buildings in Maputo, the capital city of Mozambique. The rationale behind the study lies in the need to uncover the main variables involved in the economic feasibility of adopting energy efficient practices within the building sector to help final users, policy makers and other interested groups to better understand and handle energy efficiency matters. A case study research design was used to achieve the main objective of this investigation. In this regard, a survey of households and interviews were conducted to establish the energy consumption pattern in Mozambique and its associated costs. The survey was conducted in the Kampfumo Municipality District of Maputo, and the interviews were conducted with civil engineering companies, electronic engineering, architects and building cost estimators. The questionnaires were answered by 233 households. Findings from the survey were used to perform a comparative analysis of the life cycle cost (LCC) of the buildings of the surveyed households with that of the proposed energy efficient designs, which incorporates buildings energy efficient elements and energy efficient appliances.